Nicotinic Receptors in the Brainstem Ascending Arousal System in SIDS With Analysis of Pre-natal Exposures to Maternal Smoking and Alcohol in High-Risk Populations of the Safe Passage Study - Vivekanandarajah, Arunnjah; Nelson, Morgan E.; Kinney, Hannah C.; Elliott, Amy J.; Folkerth, Rebecca D.; Tran, Hoa; Cotton, Jacob; Jacobs, Perri; Minter, Megan; McMillan, Kristin; Duncan, Jhodie R.; Broadbelt, Kevin G.; et al. (Frontiers in Neurology, 2021)
Prenatal exposures to nicotine and alcohol are known risk factors for sudden infant death syndrome (SIDS), the leading cause of postneonatal infant mortality. Here we present data on nicotinic receptor binding, as determined by 125I-epibatidine receptor autoradiography, in the brainstems of infants dying of SIDS and of other known causes of death collected from the Safe Passage Study, a prospective, multi-center study with clinical sites in Cape Town, South Africa and five United States sites, including two American Indian Reservations. We examined 14 pons and medulla regions related to cardiovascular control and arousal in infants dying of SIDS (n=12) and infants dying from known causes (n=20, 10 pre-discharge from time of birth, 10 post-discharge). Overall, there was a developmental decrease in 125I-epibatidine binding with increasing postconceptional age in 5 medullary sites (raphe obscurus, gigantocellularis, paragigantocellularis, centralis, and dorsal accessory olive [p=0.001-0.022]), three of which are nuclei containing serotonin cells. Comparing SIDS with post-discharge known cause of death (PostKCOD) controls, we found significant decreased binding in SIDS in the nucleus pontis oralis (p=0.02), a critical component of the cholinergic ascending arousal system of the rostral pons (PostKCOD, 12.1 ± 0.9 fmol/mg and SIDS, 9.1 ± 0.78 fmol/mg). In addition, we found an effect of maternal smoking in SIDS (n=11) combined with PostKCOD controls (n=8) on the raphe obscurus (p=0.01), gigantocellularis (p=0.02), and the paragigantocellularis (p=0.002), three medullary sites found in this study to have decreased binding with age and found in previous studies to have abnormal indices of serotonin neurotransmission in SIDS infants. At these sites, 125I-epibatidine binding increased with increasing cigarettes per week. We found no effect of maternal drinking on 125I-epibatidine binding at any site measured. Taken together, these data support changes in nicotinic receptor binding related to development, cause of death, and exposure to maternal cigarette smoking. These data present new evidence in a prospective study supporting the roles of developmental factors, as well as adverse exposure on nicotinic receptors, in serotonergic nuclei of the rostral medulla—a finding that highlights the interwoven and complex relationship between acetylcholine (via nicotinic receptors) and serotonergic neurotransmission in the medulla.